PENGELOLAAN RAWA GAMBUT SEBAGAI UPAYA MITIGASI BENCANA KEBAKARAN HUTAN DAN LAHAN DI PROVINSI RIAU GUNA MENDUKUNG KEAMANAN NASIONAL - Puspa Salsabila (Jurnal Manajemen Bencana (JMB), 2022)
Riau Province has the largest peatland in Sumatra, which is around 4.09 million hectares or approximately 56.1% of the total area of peatlands. Degradation of peatlands for agricultural, plantation and industrial forest plantations (HTI) activities can increase vulnerability to forest and land fire disasters (karhutla) especially if these conditions are met with natural factors, such as the El Nino climate anomaly and non-natural factors such as burning peatlands. by humans on purpose. The forest and land fires disaster in 2015 had a massive impact on neighboring countries. Efforts related to forest and land fire mitigation need to be done to prevent the 2015 disaster from happening again. In addition, mitigation efforts are considered better than extinguishing forest and land fires. The methodology used in this study is a qualitative method with data collection techniques, namely interviews, FGDs, and document studies. The results of the study found that various efforts have been made to manage peatlands as mitigation of forest and land fires in Riau Province, including by enforcing and strengthening regulations on the use of conservation peatlands, as well as carrying out peat restoration carried out by the government, communities, and companies/private sectors.